Si-Mg isotopes in enstatite chondrites and accretion of reduced planetary bodies - Sikdar, Jinia (Sci Rep, 2020)
Among the primitive meteorite classes, Enstatite Chondrites (EC) are believed to share a common origin with the Earth due to its close similarity with terrestrial mantle (Bulk Silicate Earth, BSE) for numerous isotope systematics. Si isotopes are an exception to this trend and the large δ(30)Si difference of ~0.3‰ between bulk EC and BSE has been used to argue against any major contribution of EC like planetary materials in Earth’s accretion. However, Si possess a bimodal distribution among silicate and metallic fractions of EC because of its formation under highly reducing conditions. Based on high precision Si isotope analyses in micro-milled phase separates of EH3 chondrites, here we report the presence of significantly light Si isotopes in EC-metals (δ(30)Si ≥ −6.94 ± 0.09‰, Mg/Si = ~0.001) whereas its silicate phases are isotopically heavier (Av. δ(30)Si(EC-silicates) = −0.33 ± 0.11‰, Mg/Si = ~1.01) and closer to BSE (δ(30)Si(BSE) = −0.29 ± 0.08‰). We discuss the origin of the observed Si isotope heterogeneity in terms of gas-solid interaction processes associated with metal-silicate condensation at high C/O environment (~0.83). Although the elevated δ(30)Si of BSE compared to chondrites is consistent with earlier conclusions that lighter Si has partitioned into Earth’s metallic core, our results indicate that the super-chondritic Si isotope composition of BSE does not reflect the sole consequence of high temperature-pressure core and mantle equilibration in a deep magma-ocean. Instead, Si along with Mg isotope analyses carried out in the same aliquot of EC micro-phase separates suggest that processes such as metal-silicate Si isotope fractionation at reduced nebular environment and vapor loss of lighter Si isotopes during planetary volatilization were also influential in establishing the Si isotope composition of terrestrial mantle.